1994
DOI: 10.1123/jsm.8.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Career Patterns of Athletic Directors: Challenging the Conventional Wisdom

Abstract: This study used a sociological career trajectory model to examine the career patterns of 200 male and female NCAA Division I, II, and III athletic directors. A normative career pattern derived from the literature on athletic directors was posited to compare the histories of incumbent NCAA athletic directors (ADs). The actual career experiences of ADs challenged the norm of the posited five-position sequence that begins with collegiate athlete; progresses through high school coach, collegiate coach, and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Senior managerial work in most organizations, including that in sport, is still primarily a male domain (Acosta and Carpenter 2006;Claringbould 2006;Hughes 2004;Lapchick 2006). Researchers who have focused on the skewed gender ratio of the number of executive directors/senior managers in sport organizations have looked at ways in which these individuals explain their lack of women colleagues and/or have explored individual differences between men and women athletic directors (Fitzgerald et al 1994;Hoeber and Frisby 2001;Sagas and Cunningham 2004;Whisenant et al 2002;White and Brackenridge 1985). Shaw and Frisby (2006) however, have shown that gender not only shapes identities but is an axis of power that also plays an influential role in interactions, structures, and processes of sport organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Senior managerial work in most organizations, including that in sport, is still primarily a male domain (Acosta and Carpenter 2006;Claringbould 2006;Hughes 2004;Lapchick 2006). Researchers who have focused on the skewed gender ratio of the number of executive directors/senior managers in sport organizations have looked at ways in which these individuals explain their lack of women colleagues and/or have explored individual differences between men and women athletic directors (Fitzgerald et al 1994;Hoeber and Frisby 2001;Sagas and Cunningham 2004;Whisenant et al 2002;White and Brackenridge 1985). Shaw and Frisby (2006) however, have shown that gender not only shapes identities but is an axis of power that also plays an influential role in interactions, structures, and processes of sport organizations.…”
Section: Introductionmentioning
confidence: 99%
“…This corroborated the report of Pack (2002) that 58.9% of Division III athletic directors had worked at their current institutions 10 to 29 years with between five and nine years of experience in this role at their current institutions, thus providing evidence that as athletic administrators first, and subsequently as athletic directors, they possibly preferred less of an emphasis on winning or enjoyed jobs comprised of diverse duties. Fitzgerald et al (1994) suggested career experiences of Division I athletic directors made them more likely to have been employed as assistant and associate athletic directors because of staffing arrangements of more complex organizations at this level. That is, Division I athletic directors' experiences were likely to differ from those serving in this role in Divisions II and III because of numbers of teams and athletes, philosophies of programs, and prerequisite experiences required for managing and leading more complex athletic programs.…”
Section: Discussionmentioning
confidence: 99%
“…While a few researchers (e.g., Fitzgerald, Sagaria, & Nelson, 1994;Hatfield, Wrenn, & Bretting, 1987;Spenard, 2013;Wright, Eagleman, & Pedersen, 2011) reported on the degrees and programs of study for athletic directors, studies seldom included information about other athletic administrators. In the only study found that examined educational backgrounds of other athletic administrators, Weaver and Chelladurai (2002) reported female associate athletic directors and assistant athletic directors in Divisions I and III had earned significantly higher percentages of master's degrees and doctorates than males serving in the same positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in the career patterns and profiles of female athletic administrators has been sparse. Fitzgerald, Sagaria, andNelson (1994) (1994) attempted to find a normative career trajectory of male (n= 143) and female (n=57) Athletic Directors in NCAA divisions I, II, and III. The most common, or normative, career path began in varsity athletic participation in college, followed by intercollegiate coaching, and culminated in direct advancement from coaching to the position of Athletic Director (Fitzgerald et aI., 1994).…”
Section: Women In Management Of College Athleticsmentioning
confidence: 99%